Viewing Fantastical Events in Animated Television Shows: Immediate Effects on Chinese Preschoolers’ Executive Function - Li, Hui; Hsueh, Yeh; Yu, Haoxue; Kitzmann, Katherine M. (Frontiers in Psychology, 2020)
Three experiments were conducted to test whether watching an animated show with frequent fantastical events decreased Chinese preschoolers’ post-viewing executive function (EF), and to test possible mechanisms of this effect. In all three experiments, children were randomly assigned to watch a video with either frequent or infrequent fantastical events; their EF was immediately assessed after viewing, using behavioral measures of working memory, sustained attention, and cognitive flexibility. Parents completed a questionnaire to assess preschoolers’ hyperactivity level as a potential confounding variable. In Experiment 1 (N = 90), which also included a control group, there was an immediate negative effect of watching frequent fantastical events, as seen in lower scores on the behavioral EF tasks. In Experiment 2 (N = 20), eye tracking data showed more but shorter eye fixations in the high frequency group, suggesting a higher demand on cognitive resources; this group also did more poorly on behavioral measures of EF. In Experiment 3 (N = 20), functional near-infrared spectroscopy (fNIRS) data showed that the high frequency group had a higher concentration of oxygenated hemoglobin (Coxy-Hb), an indicator of higher neurological activity consistent with a greater use of cognitive resources; this group also had lower scores on the behavioral EF tasks. The findings are discussed in reference to models of limited cognitive resources. Keywords: television, executive function, fantastical event, eye tracker, fNIRS, limited processing capacity